TFRC-Satellite: A TFRC Variant with a Loss Differentiation Algorithm for Satellite Networks - Sun, Yandong; Ji, Zhenzhou; Wang, Hui (IEEE transactions on aerospace and electronic systems, 2013)
There is an increasing number of multimedia applications featured in satellite networks. However, the performance of the transmission control protocol (TCP) friendly rate control (TFRC) protocol, which is used to transfer multimedia data in satellite networks, is much poorer than that of traditional wired networks because of the long propagation delay and the high link error rates in satellite networks. An extended end-to-end TFRC protocol, TFRC-satellite, is proposed, which uses a loss differentiation algorithm (LDA) to differentiate packet losses and to avoid TFRC's misclassifications. The LDA depends on the queuing delay calculated based on the round-trip time (RTT) measurement and makes the loss event rate calculation of the equation of TFRC more accurate. TFRC-satellite requires no modifications to the network infrastructure and other protocols. Simulations show that TFRC-satellite acquires much higher throughput compared with the original TFRC, and the utilization of the bottleneck link is improved greatly.